Impact of Fertilizers Subsidy Withdrawal on Gdp: Consequences of Fertilizers Subsidy Withdrawal on GDP and Food Security (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Previous chapters may prompt one to conclude thatfertilizer subsidy withdrawal is inevitable. It is a matter of time when it iseither completely withdrawn or its present shape goes under transformation muchunder budgetary pressure rather than the WTO obligations. The subsidywithdrawal will have many ramifications. It will impact GDP both on supply anddemand side besides denting farmer’s purchasing power and food security in termsof physical availability. This chapter will analyze the effect of subsidywithdrawal and experience of a few countries about subsidy elimination on thebasis of selected studies.